2006
DOI: 10.1366/000370206779321562
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Enhanced Gold Film over Nanostructure Surface-Enhanced Raman Substrates

Abstract: We have developed a novel class of gold multilayer, surface-enhanced Raman scattering (SERS) substrates that are capable of enhancing SERS signals by 15.3-fold over conventional gold film over nanostructure (GFON) SERS substrates, making them comparable in sensitivity to optimized silver film over nanostructure (SFON) substrates, while providing the long-term stability obtained from gold. They are fabricated by depositing 10 A thick silver oxide islands on conventional GFON substrates, followed by deposition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 43 publications
5
28
0
Order By: Relevance
“…6). 57,[77][78][79][80] Such multilayer geometries have been employed on silver island films 77 and MeFON surfaces, 57,78,79,83 demonstrating the versatility of this enhancement mechanism. In particular, by applying (10) Strobbia, Languirand, and Cullum: Recent advances in plasmonic nanostructures for sensing: a review (10) Strobbia, Languirand, and Cullum: Recent advances in plasmonic nanostructures for sensing: a review this multilayer geometry to MeFON substrates, it is possible to further enhance the original SERS signal of these substrates by over two orders of magnitude.…”
Section: Mixed Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…6). 57,[77][78][79][80] Such multilayer geometries have been employed on silver island films 77 and MeFON surfaces, 57,78,79,83 demonstrating the versatility of this enhancement mechanism. In particular, by applying (10) Strobbia, Languirand, and Cullum: Recent advances in plasmonic nanostructures for sensing: a review (10) Strobbia, Languirand, and Cullum: Recent advances in plasmonic nanostructures for sensing: a review this multilayer geometry to MeFON substrates, it is possible to further enhance the original SERS signal of these substrates by over two orders of magnitude.…”
Section: Mixed Materialsmentioning
confidence: 98%
“…These mixed material substrates include (i) dielectric materials coated with metals, [62][63][64]70 (ii) metals coated with dielectrics, 53,[71][72][73][74] (iii) semiconductors coated with metals, 75,76 and (iv) multilayered metal structures separated by dielectrics. 57,[77][78][79][80] One of the earliest and most prominent classes of these mixed material nanostructures for SERS sensing is known as core-shell nanoparticles, which consist of a dielectric core structure coated with a metallic shell [see Fig. 5(a)].…”
Section: Mixed Materialsmentioning
confidence: 99%
“…In particular, multilayer structures can improve SERS enhancement, such as "sandwich" structures with silver oxide or carbon inside and Ag or Au as both underlayer and overlayer. [24][25][26][27][28] Other researchers found that multilayer structures of Ag/Au nanostructures on the smooth metallic underlayer exhibited better SERS sensitivity compared to those without metallic underlayer (EF = 5 × 10 8 ). [29][30][31] However, the factor that governs the enhancement for multilayer structures is not very clear.…”
Section: Fabrication Of Sensitive Sers Substrates By Gladmentioning
confidence: 99%
“…The most notable types of deterministically patterned SERS substrates include (i) dense periodic arrays and gratings, [35,46,61] (ii) plasmonic structures with extremely small (5 nm or less) nanogaps [48,52,64,65], and (iii) multiscale structures and structures with complex 3D architectures [18,51,57,58,66]. Silver-coated gratings [61] and dense periodic arrays of nanoscale pillars [45,46] were among historically first SERS substrates created by means of EBL.…”
Section: Sers Substrates Created Using Deterministicmentioning
confidence: 99%
“…These types of substrate are easily controlled based on the thickness of the metal film deposited and the size of the templates used, yielding highly reproducible SERS substrates. Importantly, by depositing several layers of SERS-active metal films separated by dielectric spacers, MFONs can be used in a multilayer geometry for improved SERS enhancement by as much as 2 orders of magnitude, showing that the SERS enhancement of conventional substrates can be further increased [34][35][36]. Since SERS discovery, a large variety of substrates has been reported for its measurements as captured in recent reviews [37][38][39][40], and all of them could not be covered in this paper.…”
Section: Introductionmentioning
confidence: 98%